Bimbingan dan Konseling Sekolah - H Kamaluddin (Jurnal Pendidikan dan Kebudayaan, 2011)
The counselor plays an important role in the education system. They are regarded as school psychology. Counseling must possess and target to expand and develop the student’s potentials. They must posses good public relations and alternative solutions to students.The counselor conducts planning, carry out the programme, monitor and evaluate, and take further actions in their counseling activities. The counselor is also responsible to provide career path to the students. To conclude, the counselor act as a problem solver to the students. The Ministry of Education has given full freedom to the counselor to develop the students’ potentials and provide effective guidance and counseling. ABSTRAKPenyuluh memainkan peranan penting dalam sistem pendidikan dan mereka dianggap sebagai psikolog sekolah. Penyuluhan harus mencangkup dan mempunyai sasaran untuk mengembangkan serta memperluas potensi-potensi siswa. Mereka harus memiliki kemampuan hubungan masyarakat hubungan masyarakat yang bagus dan solusi alternative kepada para siswa. Penyuluh melaksanakan perencanaan, menjalankan program, pengawasan dan evaluasi serta melaksanakan tindak lanjut dalam kegiatan penyuluhan. Penyuluhan juga bertanggung jawab dalam menginformasikan jalur-jalur karir kepada para siswa. Penyuluhan bertindak sebagai penyelesaian masalah solver para siswa. Menteri Pendidikan telah memberikan kebebasan penuh kepada penyuluhan untuk mengembangkan potensi siswa dan menyediakan bimbingan serta penyuluhan yang efektif.